Introducing Darwin: A Graphic Guide - Jonathan Miller (Introducing (Thriplow, England), 1982)
Progress in genetics today would not be possible with Darwin's revolution, but the mysterious man who laid the rational basis for undermining belief in God's creation was remarkably timid.